Reconstructing Gender Roles in Siri’ na Pacce Culture in the Modern Era: Challenges and Opportunities - Hasni Hasni; Rezky Juniarsih Nur (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
This article examines the changes and reconstruction of gender roles in Siri’ na Pacceculture, a tradition rich in cultural and social values, in the modern era. The research employs a qualitative approach using observation, interview and content analysis techniques to gain an in-depth understanding of how gender roles in Siri’ na Pacce Culture have transformed, as well as the challenges and opportunities it faces in the modern era. The results show that Siri’ na Pacce culture has undergone a process of gender role reconstruction influenced by various factors, including globalization, modernization, and evolving social dynamics. Although there have been significant changes in gender perceptions and practices, the tradition also faces challenges in maintaining its cultural values and norms amidst modernization. The study also identifies new opportunities that have emerged in the reconstruction of gender roles in Siri’ na Pacce culture, such as women’s active participation in traditional activities that were previously considered male-dominated, as well as the adoption of more inclusive and egalitarian gender values in society. As such, this article makes an important contribution to the understanding of the dynamics of gender roles in Siri’ na Pacce culture in the modern era, as well as highlighting the challenges and opportunities faced in the reconstruction process. The implications of these findings can guide efforts to preserve and develop sustainable and inclusive local cultures in the future.